Beberapa Persoalan Berkaitan Konsep Insan Menurut Fakhr al-Din al-Razi: Some Issues Related to the Concept of Man by Fakhr al-Din al-Razi - Sa’ari, Che Zarrina; Mohd Akib, Mohd Manawi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2017)
The question of the concept of man or psychology is one of the issues that became debates among earlier philosophers such as Plato and Aristotle. In fact, it is also debated by Muslim philosophers such as Ibn Sina, al-Ghazali, al-Razi and others that coincide with the Islamic worldview. Recently, the debate of Western-based concepts of human beings who only view human beings from material aspects alone without being associated with religion are more exposed to society. The concept brought by the West is more aimed at the introduction of the essence and character of the human being from the physical point of view without seeing from the spiritual point of view. This article will highlight the initial research on some of the issues pertaining to the concept of man according to a Muslim scholar who was also described as the encyclopedic scholar, Fakhr al-Din al-Razi through his Kitab al-Nafs wa al-Ruh wa Sharh Quwahuma. In addition, his other works are also referred to the continuation of his views on the issue. Among the questions touched were the definition and the nature of the soul according to al-Razi where he explained that the soul is a jawhar of its own and it is different from the body.